Nätnyttomodellen och dess inverkan på ett distributionsnät - En studie i samarbete med Härryda Energi AB - Svensson, Johan; Wikerlund, Daniel (My University, 2006)
This report is intended to give an insight in the Network Performance Assessment Model and the parameters that is needed in the making of a fictitious grid that represents an optimal grid. A main goal is to investigate how the construction of a real grid is compared to the fictitious. One of the key parameters is how redundancy is treated in the model and to find the optimal amount of redundancy versus the costs. Further is the dimensioning of the grid of interest. The fictitious grid is based on energy whereas the real grid often is based on subscribed power and these two principles are compared and analyzed. The difference in the outcome of the model result due to variations in input data of the model is also discussed in the report.
Keywords: Elkraftteknik; Electric power engineering